The Influence of the Internship Program or Work Practices of the Business Development Agency of Syiah Kuala University on Leadership, Critical Thinking, and Communication Skills - Daska Azis; M. Hafizul Furqan; Putri Kemala Aini; Eva Murtisal (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This research investigates the phenomenon of internships, which is often criticized for being perceived as involving tasks of limited substance, often limited to activities such as photocopying and document printing. Internships are viewed as a form of experiential learning that complements theoretical knowledge gained from university education with practical application in a professional environment. The aim of this study is to examine this phenomenon, which is sometimes seen as ordinary. Quantitative research methods were employed, focusing on an associative approach with a sample of 47 individuals selected from a population of 53 using the Slovin formula. The results indicate that internships/work practices at BPBU significantly influence leadership and critical thinking skills but do not have a significant impact on communication skills. These findings provide insights into the effectiveness of internships in developing specific skills and offer perspectives for educational institutions and prospective interns in the future.